2003
DOI: 10.1007/s00122-003-1196-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of non-TIR-NBS-LRR markers linked to the Pl5/Pl8 locus for resistance to downy mildew in sunflower

Abstract: The resistance of sunflower, Helianthus annuus L., to downy mildew, caused by Plasmopara halstedii, is conferred by major genes denoted by Pl. Using degenerate and specific primers, 16 different resistance gene analogs (RGAs) have been cloned and sequenced. Sequence comparison and Southern-blot analysis distinguished six classes of RGA. Two of these classes correspond to TIR-NBS-LRR sequences while the remaining four classes correspond to the non-TIR-NBS-LRR type of resistance genes. The genetic mapping of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 53 publications
2
91
0
4
Order By: Relevance
“…Our results confirmed that the two sunflower lines XRQ and RHA340 were resistant to all P. halstedii isolates used in this study because they carry effective Pl genes against all races tested in the present study. This type of resistance may be controlled by non-TIR-NBS-LRR (Toll/interleukin-1 receptor (TIR) nucleotide-binding site leucine-rich repeat class) which clustered and linked to the Pl5/Pl8 locus for resistance to downy mildew in sunflower (Radwan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed that the two sunflower lines XRQ and RHA340 were resistant to all P. halstedii isolates used in this study because they carry effective Pl genes against all races tested in the present study. This type of resistance may be controlled by non-TIR-NBS-LRR (Toll/interleukin-1 receptor (TIR) nucleotide-binding site leucine-rich repeat class) which clustered and linked to the Pl5/Pl8 locus for resistance to downy mildew in sunflower (Radwan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The NBS region is forwarded by either a coiledcoil (CC) or Toll-interleukin1 receptor (TIR) domain, which divides the NBS-LRR genes in two classes, CC and TIR-NBS-LRR. The clusters of NBS-LRR genes were identified in PL1 locus (9), in PL6 (TIR-NBS-LRR class) (3) and in PL5/PL8 (CC-NBS-LRR class) (29,30). The cloned genes were used for development of 13 RGA based markers within PL6 (3) and 14 STS (sequence tag sites) markers within the Pl5/Pl8 locus (29,30).…”
Section: Toward Marker Assisted Selection For Fungal Disease Resistanmentioning
confidence: 99%
“…The clusters of NBS-LRR genes were identified in PL1 locus (9), in PL6 (TIR-NBS-LRR class) (3) and in PL5/PL8 (CC-NBS-LRR class) (29,30). The cloned genes were used for development of 13 RGA based markers within PL6 (3) and 14 STS (sequence tag sites) markers within the Pl5/Pl8 locus (29,30). SSR markers, closely linked to PL6, PL13 and PLarg genes were also identified (8,23,25).…”
Section: Toward Marker Assisted Selection For Fungal Disease Resistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette dernière stratégie semble avoir été expé-rimentée avec succès par Zhu et al [20] dans le cas des maladies du riz. Ces stratégies (assemblage, combinaison de gènes et alternance) sont aujourd'hui envisageables chez le pathosystème mildiou/ tournesol du fait de la découverte de plusieurs gènes Pl efficaces vis-à-vis des principales races présentes en France et de leur localisation sur la carte chromosomique [16,17,[21][22][23][24][25], ce qui a permis le développement d'outils (marqueurs) d'aide à la sélection. Dans cet article, nous présenterons les résultats d'un essai pluriannuel mettant en évidence l'impact de l'assemblage, de l'alternance ou de la combinaison de gènes sur les taux de plantes malades et sur l'évolu-tion d'une population de Plasmopara halstedii dans un dispositif contrôlé proche des conditions de culture agricoles.…”
unclassified